Evaporation trends on intervening period for different wheat establishments under soils of semi-arid tropics - BHATT, RAJAN; SINGH, PARAMJIT (Journal of Soil and Water Conservation, 2018)
Tillage methods certainly affect the soil evaporation rate by altering soil surface area. The present investigation was conducted at a sandy-loam soil of University Seed Farm, Usman, Tarn Taran to delineate the soil evaporation trends during the intervening period as affected by the residual effect of conventional (CTW) and zero till wheat plots without straw load (ZTW-SL) during wheat in 2016-2017 from 3 days after harvesting (DAH) to 7 days before puddling (DBP). CTW plots conserved more moisture than ZTW-SL plots in upper 30 cm as higher soil evaporation of 10.6% was observed in later plots. Further, soil moisture in CTW plots was 22.5%, 35.8% and 33% higher in 0-15, 15-30 and 30-45 cm, respectively compared with the ZTW-SL plots at 7 DBP. Thus, CTW plots retained prolonged and higher sum of moisture during the intervening period than ZTW-SL plots which might be useful for cultivating short intervening/fodder/summer moong crop etc. in water-stressed regions of Punjab.